2022
DOI: 10.1038/s41467-022-29525-9
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to predict abdominal age from liver and pancreas magnetic resonance images

Abstract: With age, the prevalence of diseases such as fatty liver disease, cirrhosis, and type two diabetes increases. Approaches to both predict abdominal age and identify risk factors for accelerated abdominal age may ultimately lead to advances that will delay the onset of these diseases. We build an abdominal age predictor by training convolutional neural networks to predict abdominal age (or “AbdAge”) from 45,552 liver magnetic resonance images [MRIs] and 36,784 pancreas MRIs (R-Squared = 73.3 ± 0.6; mean absolute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 88 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Symmetrically, participants on the younger end of the chronological age distribution tend to be predicted older than they are. This bias does not seem to be biologically driven (Le Goallec et al, 2022). Rather it seems to be statistically driven, as the same 60-year-old individual will tend to be predicted younger in a cohort with an age range of 60-80 years, and to be predicted older in a cohort with an age range of 60-80.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Symmetrically, participants on the younger end of the chronological age distribution tend to be predicted older than they are. This bias does not seem to be biologically driven (Le Goallec et al, 2022). Rather it seems to be statistically driven, as the same 60-year-old individual will tend to be predicted younger in a cohort with an age range of 60-80 years, and to be predicted older in a cohort with an age range of 60-80.…”
Section: Methodsmentioning
confidence: 99%
“…We used the FUnctional Mapping and Annotation (FUMA) tool for identifying the independent loci of the GWAS results and mapping them to their closest genes (Watanabe et al, 2017) as we recently performed in a prior study on another organ dimension (Le Goallec et al, 2022). Specifically, we identify (1) the loci associated with each of the traits, and the (2) nearest protein coding genes.…”
Section: Identification Of Snps Associated With Accelerated Eye Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD is linked not just to metabolic abnormalities but also bad lifestyle choices ( 5 ). Also, population aging accelerates the progression of NAFLD ( 10 , 11 ). Thus as evidenced by the abdominal age predictor, AbdAge model, which was developed on liver MRI images and revealed that with advanced age, the liver becomes darker, its volume diminishes, and blood flow declines ( 10 ).…”
Section: Introductionmentioning
confidence: 99%